2011
DOI: 10.1159/000323184
|View full text |Cite
|
Sign up to set email alerts
|

Adapted T Cell Interferon-Gamma Release Assay for the Diagnosis of Pleural Tuberculosis

Abstract: Background: Better and more rapid tests are needed for the diagnosis of tuberculous pleural effusion (TPE), given the known limitations of conventional diagnostic tests. Objectives: To estimate diagnostic accuracy of the QuantiFERON-TB Gold In-Tube (QFT-GIT) test (and its components) using data-derived cutoffs in pleural fluid. Methods: The QFT-GIT test was performed on whole blood and pleural fluid from 43 patients with TPE and 29 control subjects (non-TPE). To achieve the objective, QFT-GIT test, estimating … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(24 citation statements)
references
References 50 publications
0
24
0
Order By: Relevance
“…First, the T-SPOT.TB assay but not the QFT test requires a mandatory number of mononuclear cells, which might ensure a more accurate result even in patients with low T cell titers, such as those with HIV infection or another immunodeficiency. Second, more accurate results may be obtained when performing the IGRA in PF, the active infection site of tuberculous pleurisy, because of the compartmentalization of the immune response of Th1 cells in TB infection12,16-18,22. Third, in our study, the QFT-G test had more indeterminate interpretations than the T-SPOT.TB test in both PF and blood, which might reduce its diagnostic accuracy.…”
Section: Discussionmentioning
confidence: 71%
See 2 more Smart Citations
“…First, the T-SPOT.TB assay but not the QFT test requires a mandatory number of mononuclear cells, which might ensure a more accurate result even in patients with low T cell titers, such as those with HIV infection or another immunodeficiency. Second, more accurate results may be obtained when performing the IGRA in PF, the active infection site of tuberculous pleurisy, because of the compartmentalization of the immune response of Th1 cells in TB infection12,16-18,22. Third, in our study, the QFT-G test had more indeterminate interpretations than the T-SPOT.TB test in both PF and blood, which might reduce its diagnostic accuracy.…”
Section: Discussionmentioning
confidence: 71%
“…Comparing the diagnostic performance of either IGRA between PF and blood samples in the TB pleurisy, some clinical studies showed inconsistent results, depending on the type of assay, patient population, and incidence of TB infection12,15-20. In countries with a low TB burden, the IGRA has superior diagnostic accuracy in PF than in blood, whereas the reverse is true in intermediate-to high-burden countries19,20.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In our case, the patient was assumed to have TB pericarditis and pleurisy due to lympho-dominant exudate with a high ADA level on effusion analysis. Although she had a negative result of IGRA, the negative predictive value of the test of peripheral blood is known to be relatively low in the diagnosis of TB pleurisy (17). Regarding the relationship between ADA and Behçet's disease, several studies have shown that plasma ADA levels are increased in patients with…”
Section: A B Discussionmentioning
confidence: 99%
“…Ariga et al (Ariga et al, 2007) reported that IGRAs showed a modest sensitivity of 78% and a specificity of 70% in the diagnosis of pleural TB, and Ates et al (Ates et al, 2011) reported a similar sensitivity of 70% and a lower specificity of 52%. Among 15 patients with pleurisy in our study, the IGRA showed a lower sensitivity of 38.5% and a specificity of 50.0%.…”
Section: Accepted Manuscriptmentioning
confidence: 99%